37. EVALUATION OF THE STABILITY OF LYOPHILIZED PLASMA SAMPLE IN THE PROFICIENCY TESTING SCHEME FOR DETECTING ANTIGENS OF NS1 VIRUS DENGUE (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the stability of lyophilized plasma items to detect Dengue virus NS1 antigen according to ISO/IEC 17043:2023 and ISO 13528:2022 standards for application in proficiency testing (PT) scheme.Method: Experimental research. Lyophilized plasma items including 2 batches: batch A (positive samples for Dengue virus NS1 antigen), batch B (negative samples for Dengue virus NS1 antigen) after being checked for homogeneity, will be evaluated for short-term and long-term stability according to ISO 13528. Select a random sample through Microsoft Excel 16 software. Use one-way analysis of variance (One-way ANOVA) to evaluate the homogeneity of the samples.Results: At short-term conditions (transportation time), the items are stable up to 7 days. At longterm conditions, when stored at -20o C, 0o C, 2 - 8o C, the items are stable up to 90 days.Conclusion: The lyophilized plasma item to detect Dengue virus NS1 antigen achieved stability during transportation and storage conditions to meet ISO/IEC 17043:2023 and ISO 13528:2022 standards for application in proficiency testing scheme.
Keywords: Proficiency testing, NS1, Dengue virus, Dengue fever, stability